Implementation of Multicultural Values in Developing Student Tolerance - Ahmad Falah; Taufikin Taufikin; Moh. In’ami (Journal La Edusci, 2026)
Cultivating tolerance attitudes across various groups, including adolescents, is essential for fostering harmony in every aspect of society. This importance is demonstrated in schools throughout Indonesia. SMK Raden Umar Said and SMK Duta Karya exemplify schools that consistently display tolerance, hospitality, and acceptance of diverse ethnicities and cultures. These values are manifested through various activities implemented both curricularly and co-curricularly. This significance necessitates the implementation of this research. The study seeks to analyze and describe the implementation processes conducted by the schools and the impacts experienced by students and the surrounding environment regarding the multicultural value implementation. This research employs a qualitative approach. The researchers reveal the processes and impacts experienced by students and the surrounding environment through data analysis techniques obtained from interviews with school principals, teachers, students, documentation, and in-depth observation. The research findings indicate: 1) the principles of instilling multicultural education values in schools are based on several principles, namely openness, tolerance, unity in diversity, and Islam rahmatan lil'alamin; 2) the implementation of instilling multicultural education values is patterned into two categories: multicultural knowledge and multicultural feeling. Multicultural knowledge is provided through several activities such as religious activities, Quranic recitation, Islamic holiday celebrations, and PAI subject learning in classrooms. Meanwhile, multicultural feeling is instilled through daily student activities.